Analysis of The Impact of Flood on Residential Building Damage in Rawang Spread District, Sungai Penuh City, Jambi - Riskyani, Mella Anggina; Ramadhan, Miftahul Akbar; Fajri, Muhammad Ridho (Sinektika: Jurnal Arsitektur, 2025)
Indonesia is known for being prone to disasters, and over the past decade, they have impacted 942,697 houses. Among these disasters, floods rank as the second most impactful in the country. In Sungai Penuh City, flooding occurs annually and has become the primary concern for the local government. Since the start of 2024, three of Sungai Penuh's eight sub-districts have endured prolonged floods due to heavy rainfall in the Batang Merao Watershed, leading to water overflow and settlements along the riverbank. This research analyses the damage inflicted by the Batang Merao River floods between December 2023 and April 2024 on house buildings in the Hamparan Rawang District. The data collection method employed was qualitative, involving observation and interviews. Subsequently, the data underwent quantitative analysis to derive a building damage index. The study focused on three categories of building components: structural, architectural, and utility. Among the 86 respondents, the structural damage index was 16.76 (light), architectural damage was 16.76 (light), and utility damage was 16.90 (light). The overall building damage index, calculated from these results, is 12.58 (light).